Educational Technology Based on Artificial Intelligence in Supporting Distance Learning in Arabic Language Learning in Higher Education - Salam, Muhammad Yusuf; Fitri, Silva; Zulan, Hafifa (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Nowadays, technological developments are increasingly widespread. In fact, the use of artificial intelligence-based technology is on the rise. Artificial intelligence technology is a managed tool that can facilitate human work. Artificial intelligence technology gets a high position in the educational process and even experiences development from time to time, namely from the school level to the college level. As the development of artificial intelligence technology began to be applied in the learning process. The purpose of this research is to find out that artificial intelligence technology can support distance learning in Arabic language learning in college and greatly help students in doing assignments. The method in this study is to use quantitative research methods where the data obtained is through the distribution of a questionnaire in which there are statements that will be answered by students. The questionnaire was distributed by utilizing the Google Form application. The results of this study explain that artificial intelligence technology is very suitable to be applied in the distance learning process and can support learning activities carried out in Arabic language learning in college. The conclusion of this research is that technology based on artificial intelligence is very appropriate to be used in the distance learning process, namely in Arabic language learning, because the use of intelligence technology is more effective and efficient and greatly helps humans in doing work. The limitation of this study is that researchers only conducted this research at the college level which in fact the learning process is carried out remotely. The researcher hopes that future researchers can develop the Arabic language learning process at a more advanced stage. This study also recommends to future researchers to make this research a reference in conducting research related to artificial intelligence technology.